Utilizing Visual Literacy Competence as a Strategy in Teaching Descriptive Writing - Hermansyah; Rahayu Puji Haryanti; Sri Wahyuni; Frimadhona Syafri (Universitas Tidar, 2023)
Utilizing visual literacy competence, a strategy is very helpful in order to make students’ feel better in writing a descriptive paragraph, since, it is help students to develop their idea, thinking and imaging a vocabulary use and having an organization of idea come up into their mind. The purpose of this paper is to know the effectiveness of utilizing visual literacy competence as a strategy in teaching descriptive paragraph writing, and to know the students’ perception toward utilizing visual literacy competence as a strategy in teaching descriptive paragraph writing. Mixed method used in this research. The result came from the test given in one-group-pretest and posttest, and qualitative data from the questionnaire given to 22 students of Vocational High School students. It can be drawn that the efficiency of using visual literacy in the classroom to teach students how to write descriptive paragraphs, as well as the attitudes of the students toward the use of visual literacy in the classroom to teach students how to write descriptive paragraphs. Most of students are agreed to utilize visual literacy as strategy in teaching descriptive paragraph writing is really effective to use.